Health Financing in the Republic of Gabon - Saleh, Karima; Couttolenc, Bernard F.; Barroy, Helene (Washington, DC: World Bank, 2014)
This is a review of the health financing situation in the Republic of Gabon. The book reviews the situation in the country under the lens of the principles of health financing: revenue mobilization for health, risk pooling, and purchasing services. The book also estimates the fiscal space in health that is, looking at options that can increase resources for health within a macroeconomic and fiscal context. Universal health coverage has been defined as a situation where all people who need health services (prevention, promotion, treatment, rehabilitation, and palliative) receive them, without undue financial hardship. Universal health coverage consists of three inter-related components: (i) the full spectrum of quality health services according to need; (ii) financial protection from direct payment for health services when consumed; and (iii) coverage for the entire population. Because of Gabon's commitment to universal health coverage, certain segments are calling for additional resources for this sector. As a result, the country is grappling with the following: (i) how are resources being spent, (ii) is there room for a more efficient allocation of current resources, or (iii) is there an urgent need to mobilize additional resources to meet the goal. This book attempts to diagnose the situation and offer additional information to enlighten and fuel the debate. The book has six chapters: chapter one gives background and objectives. Chapter two provides an overview of the country s health status and service use patterns. Chapter three provides an overview of health financing systems and outputs. Chapter four provides an overview of the national health insurance and social security (caisse nationale d'assurance maladie et de garantie sociale) (CNAMGS). Chapter five provides fiscal space analysis for health. Finally, chapter six provides the reform issues and policy options in health financing.